I'll see you in Ijebu [book with audioplayer] - Emenanjo, Bunmi ([Library Ideas, LLC], 2024)
"A Catholic girl growing up in the bustling city of Lagos, Nigeria takes a trip to spend a week with her Muslim extended family in the countryside town of Ijebu to celebrate Eid al-Adha. Her days in Ijebu are filled with celebrations, traditions and special time connecting with family. Breathtaking illustration and poetic writing draws the reader into the sensory experience of celebrating Eid in Nigeria, while detailed endmatter includes information about Nigeria and Eid al-Adha, recipe for Nigerian puff puff and more."--